SPECIFIC AND NON-SPECIFIC PARAMETERS OF SIMPLICIA AND ETHANOLIC EXTRACT OF PRASMAN LEAVES (AYAPANA TRIPLINERVIS) - SARI, SASMITA RETNO; ELYA, BERNA; BASAH, KATRIN (International Journal of Applied Pharmaceutics, 2020)
Objective: Ayapana triplinervis (Vahl) R.M.King and H. Rob. leaves can be applied as a diuretic and as an antioxidant. Based on its medicinal properties, A. triplinervis can be used as traditional medicine. Therefore, its quality and safety should be guaranteed, which could be verified based on the outcomes of standardization processes. The aim of the present study was to evaluate some specific and non-specific parameters of simplicia and 70% ethanolic extracts of A. triplinervis leaves from three regions in Indonesia. Methods: The samples were macerated using 70% ethanol. Results: With regard to the specific parameters of A. triplinervis simplicia, the total water-soluble extract was 18.69–29.30%, the total ethanol-soluble extract was 7.73–11.78%, and the total flavonoid content was 3.31–4.10, expressed as mg rutin equivalent (RE)/g simplicia. With regard to the nonspecific parameters, the total drying losses were 13.61–14.55%, the total ash content was 11.54–11.83%, and the total acid insoluble ash content was 1.90–2.66%. In the extracts, the total flavonoid content was 14.94–22.41 expressed as mg RE/g extract, while for the non-specific parameters, the total water content was 11.07–12.66%, the total ash content was 10.55–10.89%, and the total acid insoluble ash content was 0.25–0.32%. Conclusion: The parameters identified could be used to determine the safety and stability of extracts and simplicial before administration to treat various ailments.